Some Facts About Constative And Performative Sentences, And Their Experimental-Phonetic Analysis - Alı, Mamedlı Aysel (Advances in Social Sciences Research Journal, 2017)
The article deals with the investigation of performative and constative sentences. The famous essay of J.Austin “How to do things with Words” has been investigated and analyzed widely. The meaning of the term ‘speech act’ has been exemplified in the article as well. The reasons of calling sentences performatives and constatives have also been analyzed in the article. According to J.Austin the name ‘performative’ is derived from ‘perform, the usual verb with the noun ‘action’: it indicates that the issuing of the utterance is the performing of an action – it is not normally thought of as just saying something. The reason of calling some kinds of sentences ‘constative’ has been explained basing on the theories of J.Austin. The experimental-phonetic analyses of some performative and constative sentences have been carried out too. The results of the experiment have been shown in tables, and the calculations have been performed due to mathematical method.